Factors in infertility score on referral and non-referral cases who underwent In Vitro Fertilization (IVF) treatment at a fertility clinic in Surabaya, Indonesia - Nadhif Rashesa Brahmana; Ashon Sa’adi; Rina Yudiwati (Majalah Obstetri & Ginekologi, 2022)
HIGHLIGHTS 1. Infertility score should be identified to obtain successful outcome of In Vitro Fertilization (IVF).2. Factors considered in determining the infertility score were examined.3. Each factor in infertility score (e.g, age, duration of infertility, menstrual cycle, pelvic pain etc.) has its own different degrees of severity that influence the outcome of IVF.   ABSTRACT Objectives: To examine the factors used in infertility score on referral and non-referral cases who underwent IVF treatment at Fertility Clinic of Graha Amerta, Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, in 2014-2016 Materials and Methods: This research was a descriptive analytic retrospective study using secondary data from medical records at Fertility Clinic of Graha Amerta in 2014-2016. With a total sampling technique, a total of 342 referral and non-referral infertility cases were obtained. The variables in this study were the factors considered in infertility score. Results: From a total of 342 cases, 44% had the wife's age in the range of 30-35 years, 80.1% had an infertile duration of > 3 years, and 54.7% had one type of pelvic pain, 68.4% still had regular menstrual cycles, and about 76% did not have a history of pelvic infection. On sperm analysis factor, there were 27.5% of men who fell into the severe category according to infertility score. There was a significant difference in the duration of infertility and sperm morphology in referral and non-referral cases. Conclusion: Infertility score can be useful because each case has its own infertility factors with different degrees of severity, which leads to infertility.